ANALISIS READINESS MAHASISWA BARU DALAM PEMBELAJARAN DARING DI UIN SUNAN KALIJAGA YOGYAKARTA - Aulia Faqih Rifa'i; Sumarsono Sumarsono (JURNAL TEKNIK INFORMATIKA, 2020)
As an impact of Covid-19, the learning methods is shifting from conventional into e-learning. Therefore, UIN Sunan Kalijaga Yogyakarta as an educational institution have to implement online lectures for all students. This event causes the first year students to not having the opportunity to understand how lectures work. On the other hand, lecturers and the university did not yet have a picture of the readiness of new students to study with e-learning method. For that case, the university needs to know if the students are ready to be doing e-learning lectures. This descriptive quantitive research uses a questionnaire and e-learning readiness factors by Chapnik [1] to see the readiness of new students. As a result, the score of new students e-learning readiness is 45.09. Thus, new students of UIN Sunan Kalijaga Yogyakarta are not ready enough for studying in e-learning methods. This research also provides suggestions about how e-learning methods should be done for the lecturers.